Internalisasi Nilai-Nilai Pendidikan Agama Islam melalui Kegiatan Ekstrakurikuler Pramuka: Internalization of Islamic Religious Education Values ??Through Scout Extracurricular Activities - Tazkirah, Siti; Ruslan, Ruslan; Nasaruddin, Nasaruddin (Thawalib: Jurnal Kependidikan Islam, 2024)
The internalization of Islamic Religious Education values among students often faces challenges in linking religious theory with everyday life practices, especially in conveying and applying those values outside of formal lessons. This study aims to examine the process and strategies of internalizing Islamic Religious Education values through extracurricular scouting activities at SMP Negeri 6 Bima City. The study uses a qualitative approach, with data collection techniques including interviews, documentation, and observation. The findings show that the process of internalizing Islamic Religious Education values through scouting activities includes various activities such as Drill Regulations, Knots, Morse Code, Semaphore, Exploration, and Campfires. Supporting factors in the scouting extracurricular activities include the psychological factors of participants, the role and support of the school principal, and the availability of facilities and infrastructure that support the smooth running of these activities. All these factors play a crucial role in the successful internalization of religious values.